ANALYSIS OF COST OF PRODUCTION USING METHOD FULL COSTING AND VARIABLE COSTING AT THE COFFEE HOUSE ROOM IN 2022 - Bani Zamzami (International Journal Management and Economic, 2024)
This scientific writing aims to determine the calculation of the cost of goods produced at Ruwang Coffee House using the full costing and variable costing methods. Determination of the cost of goods produced is very important in determining competitive prices, so that the business can compete in the market and can increase business income. The data collection methods used in this research are interviews and observations. Interviews were conducted directly to business owners. This research uses quantitative data and the data used is primary data, where the data is obtained directly by Ruwang Coffee House. The data obtained in the form of the number of sales, raw material costs, labor costs, and factory overhead costs. From the research that has been done, the authors conclude that the calculation of the cost of goods produced using the full costing method has a greater value when compared to using the variable costing method, this is because the full costing method charges all factory overhead costs, the full costing method is better used than using the variable costing method.